Emergent Anthropometric Indices in Differential Prediction of Prehypertension and Hypertension in Mexican Population: Results according to Age and Sex - Oscar Zaragoza-García; Ilse Adriana Gutiérrez-Pérez; Pedro Delgado-Floody; Isela Parra-Rojas; Daniel Jerez-Mayorga; Christian Campos-Jara; Iris Paola Guzmán-Guzmán (International Journal of Hypertension)
Background. Hypertension (HTN) is recognized as a significant public health problem in the world. The objective of this study is to evaluate emergent anthropometric indices as predictors of preHTN and HTN according to age and sex in a sample of Mexican adults. Methods. A cross-sectional study was conducted in 1,150 participants aged 18–80 years old. Anthropometric data and blood pressure measurements were analyzed. Comparisons between men and women were carried out by independent analysis. Cutoff points for each emergent anthropometric index were obtained using the values’ upper second and third tertiles. Logistic regression models and receiver operating characteristics curve analyses were used to assess the association and the predictive value of several emergent anthropometric indices with the presence of preHTN and HTN. Results. The prevalence of preHTN and HTN was 29.74% and 14.35%, respectively. In a logistic regression analysis adjusted by age and sex, the body roundness index (BRI) (OR = 2.08, p<0.001) and conicity index (CI) (OR = 1.37, p=0.044) were associated with preHTN, while CI (OR = 2.47, p<0.001) and waist to height squared (W/Ht2) (OR = 2.19, p<0.001) were associated with HTN. Furthermore, in both sexes, BRI was the main predictor of preHTN (AUC: 0.634 and 0.656, respectively). Particularly, according to sex and age range, the predictive emergent anthropometric indices in men were the body shape index (ABSI) and waist to height cubic (W/Ht3) (AUC = 0.777 and 0.771, respectively), whereas in women, the predictors were CI and ABSI (AUC = 0.737 and 0.729, respectively). In men ≤40 years old, central body fat indices were predictors of preHTN and HTN, but in men >40 years old, the predictor indices were W/Ht3 and W/Ht2. In women ≤40 years, the pulse mass index (PMI) was the best main predictor (AUC = 0.909) of HTN. Conclusion. CI, PMI, W/Ht3, W/Ht2, and ABSI could represent differential predictors of preHTN and HTN between men and women according to age range.